Rol de enfermería en los primeros 1000 días de vida. - Coro Choro, Josselyn Isayuri (2025)
This research analyzed the role of nursing in the primary prevention of childhood mahutrition in the first 1000 days of life in Ecuador, considering the epidemiological profile and nursing interventions to promote health and prevent malnutrition Methodology: It was necessary to conduct a bibliographic review with a documentary and descriptive approach based on a review of scientific literature in databases such as Google Scholar, Scielo, Dialnet, ELSEVIER, and PubMed. The researcher considered the following inclusion criteria: review articles with full- text availability published from 2019 to 2024, studies conducted in Latin America, and articles related to nursing performance during this critical period. Results: Nursing professionals actively protect child development from conception to two years of age through community activities, information campaigns, and the promotion of healthy lifestyles, highlighting the importance of education as their primary tool Conclusions: The role of nursing during the first 1,000 days of life is based on promotional interventions that are consistent with the functions assigned in their daily work, such as training mothers on appropriate diets during pregnancy, correct care practices, attendance at check-ups during pregnancy and for the child, among others. Furthermore, to prevent childhood mahutrition, mrsing implements interventions during pregnancy, such as prenatal check-ups, while infants receive immunizations, metabolic screening, and micronutrient supplementation Keywords: Childhood Malnutrition, Role of the Nurse, Nursing Education, Nutrition Programs